Camel performance on domestic and foreign banks in Malaysia - Voon, Soon Ping. (2013)
Using CAMEL analysis, the aim of this study is to examine and compare the performance of the Malaysian's domestic banks and foreign banks in the financial sector.The CAMEL analysis consists of items which are Capital adequency, Assets quality, Management efficiency, Earning quality and Liquidity. Measuring the performance of the banks in terms of Capital adequacy, Assets quality, Management efficiency, Earning quality and Liquidity (CAMEL) for both domestic and foreign banks are able to provide detailed performance of the banks in the banking system.